Introducing an application of a charged coupled device (CCD) in an optical tomography system - Juliza Jamaludin; Rahim R.A.; Rahim H.A.; Rahiman H.F.; Muji S.Z.M.; Fadzil N.S.M.; Ling L.P.; Jumaah F.; Ahmad A.; Ayob N.M.N.; Hong L.E. (Penerbit UTM Press, 2024)
Vol. 73 No. 3: Special Issue on Sensor Technology and Control System Applications